Rapid Market Appraisal (RMA) for Fodder Products - Wandschneider, T. (International Livestock Research Institute, 2008)
The training course “Rapid Market Appraisal for Fodder Products” was conducted under the auspices of the IFAD Fodder Adoption Project. The training was provided by Tiago Wandschneider of the International Center for Tropical Agriculture (CIAT). Thirteen people from Ethiopia, Syria, Vietnam and the United Kingdom participated in the course. The main objective of the course was to equip participants with basic knowledge and skills that will enable them to contribute to future market research activities under the IFAD fodder Adoption Project. Emphasis was given to providing participants with an understanding of important marketing concepts and key features of agricultural markets and to guiding them through the different steps of a Rapid Market Appraisal (RMA).